Stimulation of Fengycin-Type Antifungal Lipopeptides in Bacillus amyloliquefaciens in the Presence of the Maize Fungal Pathogen Rhizomucor variabilis - Zihalirwa Kulimushi, Parent; Argüelles Arias, Anthony; Franzil, Laurent; Steels, Sébastien; Ongena, Marc (Frontiers in Microbiology, 2017)
Most of bacterial isolates belonging to the Bacillus amyloliquefaciens subsp. plantarum clade retain the potential to produce a vast array of structurally diverse antimicrobial compounds that largely contribute to their efficacy as biocontrol agents against plenty of plant pathogens. In that context, the role of cyclic lipopeptides (CLPs) has been well documented. Different physico-chemical factors inherent to the rhizosphere ecology are known to modulate CLP production but still little is known about the impact of other soil-inhabiting microbes on the expression of these molecules. In this work, we investigated the antagonistic activity developed by this bacterium against Rhizomucor variabilis, a rare pathogen isolated from diseased maize cobs in Democratic Republic of Congo. Our data show that fengycin-type CLPs are the major compounds involved in the inhibitory activity but also that production of the latter is significantly upregulated upon perception of the fungus compared to pure cultures. B. amyloliquefaciens is thus able to perceive fungal molecules that are emitted and, as a response, up-regulates the biosynthesis of some specific components of its antimicrobial arsenal.